Statistical analysis of electrodeposited nickel coating to S275JR grade mild steel. (2021) - Govindan, S.; Boopathi, M.; Venkatesh, A.P.; Maridurai, T.; Sathish, T.; Balakrishnan, E.
Abstract: In recent trends the electrodeposition process are very important of the soft material as well as hard material to avoid the corrosion resistance. For this research, S275JR mild steel specimens are considered as a base material for the coating A thin film Nickel coatings are made on the S275JR mild steel with the concentration of electrodepositing route. Due to this electrodeposition work modified the surface structure, improves the mechanical properties and turned to high corrosion resistance in nature. Three process parameters are considered for this work namely: voltage rate, stirring speed and time. The response values of micro hardness and mass of deposition are analyzed by L9 orthogonal array effectively. Enhanced micro hardness and mass of deposition of S275JR mild steel is obtained by the influence of two major parameters such as time period and the stirring speed. Rank order and delta values are point out the parameters precedence. ANOVA statistical approaches informed the process factors role and contribution effectively.